Immunosuppressive drugs and their aerosol delivery for COVID-19 treatment - V. I. Kobylyansky (Фундаментальная и клиническая медицина)
Despite numerous efforts of healthcare, the incidence of COVID-19 and its fatal complications remains unacceptably high. As COVID-19 pathophysiology is notable for an uncurbed immune response, its treatment protocols routinely include immunosuppressive drugs such as corticosteroids, cytostatic drugs, calcineurin inhibitors, and monoclonal antibodies. Here we review the efficacy of the latter 3 drug classes, in particular inhalation preparations, in COVID-19 treatment and SARSCoV-2 elimination as well as their potential advantages and drawbacks. Efficacy of cytostatic drugs and calcineurin inhibitors in the treatment of airway inflammation in COVID-19 remains unconfirmed. Promising agents in this regard are biologics, including monoclonal antibodies and purinergic agents.